2010
DOI: 10.1111/j.1574-6968.2009.01849.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a gene coding for a deglycosylating enzyme inHypocrea jecorina

Abstract: An enzyme with mannosyl glycoprotein endo-N-acetyl-beta-D-glucosaminidase (ENGase)-type activity was partially purified from the extracellular medium of the mould Hypocrea jecorina (Trichoderma reesei). Internal peptides were generated and used to identify the gene in the T. reesei genome. The active enzyme is processed both at the N- and at the C-terminus. High-mannose-type glycoproteins are good substrates, whereas complex-type glycans are not hydrolysed. The enzyme represents the first fungal member of glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 39 publications
2
56
1
Order By: Relevance
“…Some members of the chitinases were only identified based on the recent genome analyses. As described more recently, some members of GH family 18 do not exhibit chitinase activity but instead have endo-N-acetlyglucosaminase (ENGase) activity and cleave between two N-acetylglucosamine residues in the carbohydrate antennae of proteins (336). They are therefore involved in protein deglycosylation.…”
Section: Cazymesmentioning
confidence: 99%
“…Some members of the chitinases were only identified based on the recent genome analyses. As described more recently, some members of GH family 18 do not exhibit chitinase activity but instead have endo-N-acetlyglucosaminase (ENGase) activity and cleave between two N-acetylglucosamine residues in the carbohydrate antennae of proteins (336). They are therefore involved in protein deglycosylation.…”
Section: Cazymesmentioning
confidence: 99%
“…Group A is predicted to include mainly exochitinases (Gruber & Seidl-Seiboth, 2012), although the A-II subgroup member Cfcl from Aspergillus niger exhibits exo-b-N-acetylglucosaminidase activity (van Munster et al, 2012). Characterized group B chitinases are mostly endo-acting enzymes, while the B-V group contains members with endo-b-N-acetylglucosaminidase (ENGase) activity (Stals et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Flammulina velutipes Endo FV [137] Hypocrea jecorina (Trichoderma reesei) Endo T [136] A gene encoding tomato ENGase LE was identified and expressed in E. coli in which the substrate specificity remained identical to the native enzyme [121]. Moreover, real-time PCR demonstrated that the gene expression did not vary during ripening and thus that the ENGase LE activity was ubiquitously expressed.…”
Section: Plant N-glycan-engasesmentioning
confidence: 96%
“…However, this de-N-glycosylation activity is widely distributed [137] and several highly homologous proteins or gene products are found among ascomycetes [136]. Both Endo T and Endo FV hydrolyze high-mannose type structures as observed in fungal and yeast glycoproteins, but do not release complex type N-glycans [136,137]. Endo T was shown to be responsible for the microheterogeneity observed for H. jecorina cellulases and hemicellulases [138].…”
Section: Fungal N-glycan-engasesmentioning
confidence: 99%
See 1 more Smart Citation